Technology and characterization of p-i-n photodetectors with DQW (In,Ga)(As,N)/GaAs active region - Pucicki, Damian; Zborowska-Lindert, Iwona; Ściana, Beata; Radziewicz, Damian; Boratyński, Bogusław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
Double quantum well (DQW) (In, Ga)(As, N)/GaAs p-i-n photodetectors, grown by solid source molecular beam epitaxy using a radio-frequency plasma source for nitrogen with absorption for wavelengths above 870 nm have been investigated. The active region of the photodetectors contained two very thin absorption layers: 10.5 nm Ga(As, N) (structure #DP02) or 4 nm (In, Ga)(As, N) (#DP03). In spite of this, photodetectors exhibited high sensitivity (0.0525 A/W for 980 nm) for wavelength greater than the absorption edge of GaAs (870 nm). The dark current of photodetectors did not exceed 0.1 μA.
Optica Applicata, Vol. 37, 2007, nr 4, s. 415-421
Keywords: optyka; p-i-n photodetector; diluted nitrides; (In,Ga)(As,N); GaAs-based photodetectors; double quantum well (DQW) heterostructures